Modification of poly maleic anhydride by addition of different aldo mono saccharides - O.Al-Tamimi, Entesar; M,Al-Mouamin, Thanaa; J.Kadoom, Zaidoon (Iraqi Journal of Science, 2023)
This research includes new series of polymers were synthesized starting from polymerization of poly maleic anhydride (3), which were mono esterfication with absolute methanol to give polymer (4 ), then the acid side chlorination with thionyl chloride to give polymer (5) , which was subjected to esterfication with two different protected sugar moiety (1 and 2 ) to afford modified polymers (6 and 7). Furthermore the hydrazide polymers ( 8 and 9) were prepared through addition of hydrazine hydrate to polymers ( 6 and 7 ), which upon condensation with different free mono saccharides to give the target polymers( 10-13) respectively. The prepared polymers identified by physical properties and spectral methods (FT-IR ,1H-NMR,13C-NMR) .